Minat Berhubungan Dengan Bank Syari’ah dan Wilayah Potensial Pengembangan Bank Syari’ah di Daerah Istimewa Yogyakarta - Muhammad Muhammad (Universitas Islam Indonesia, 2007)
This study is concerned with: (1) the societies interest to Islamic banking in Daerah Istimewa Yogyakarta; (2) the area of Daerah Istimewa Yogyakarta that have still possibilities to developed Islamic banking. The research methods was conducted for data collecting with questionary and interview. The data analysis was conducted with (1) descriptive analysis by the frequency distribution, and. (2) the factor analysis. The factor analysis with Binary Logistic Regression technique was conducted for analysis the factors that influence societies interest to Islamic banking. The result of research view: (1) the society interest to Islamic banking influenced by eight factors, that are: (a) Religiousity; (b) knowledge of existing Islamic banking; (c) Opinion about bank interest; (d) degree of education; (e) kind of job; (f) income level (about: 500.001 – 1000.000); (g) Preferency to Islamic banking, and (h) knowledge about product and Islamic banking mechanism. (2) the area have high rating for Islamic banking development is Sleman District. In other word, the Sleman district has potensial area for Islamic banking in Daerah Istimewa Yogyakarta.Keywords: Minat, Wilayah Potensial, Riba, Bunga Bank